Answer:
9(4+3)
Step-by-step explanation:
The GCF of 36 and 27 is 9. Dividing 36 and 27 by 9, I used the distributive property and got the equation 9(4+3)
Answer: 3x - 7
x = some input number
3x = triple the input
3x - 7 = difference of triple the input and 7
If I'm reading the question right, you have
and you have to find
The limits exist if the limits from either side exist. We have
and
The function f(x) is a piecewise function. The limit as x approaches 5 equals 2 and the limit as x approaches 6 does not exist as the values from both sides are not the same.
The function f(x) given is a piecewise function which is defined differently on different intervals of x.
First let's graph these three conditions:
Next, we'll find the specified limits:
#SPJ11
Answer:
D. F(x) = 2(x-3)^2 + 3
Step-by-step explanation:
We are told that the graph of G(x) = x^2, which is a parabola centered at (0, 0)
We are also told that the graph of the function F(x) resembles the graph of the function G(x) but has been shifted and stretched.
The graph of F(x) shown is facing up, so we know that it is multiplied by a positive number. This means we can eliminate A and C because they are both multiplied by -2.
Our two equations left are:
B. F(x) = 2(x+3)^2 + 3
D. F(x) = 2(x-3)^2 + 3
Well, we can see that the base of our parabola is (3, 3), so let's plug in the x value, 3, and see which equation gives us a y-value of 3.
y = 2(3+3)^2 + 3 =
2(6)^2 + 3 =
2·36 + 3 =
72 + 3 =
75
That one didn't give us a y value of 3.
y = 2(3-3)^2 + 3 =
2(0)^2 + 3 =
2·0 + 3 =
0 + 3 =
3
This equation gives us an x-value of 3 and a y-value of 3, which is what we wanted, so our answer is:
D. F(x) = 2(x-3)^2 + 3
Hopefully this helps you to understand parabolas better.
Answer:
I actually needed help with the answer but now I think about it the answer is answer C. $50
Step-by-step explanation:
Answer:
I think that it is B. 49.99
Step-by-step explanation:
Answer:
Step-by-step explanation:
step one:
let us re-write the expression in mathematical terms for clarity
we have the expression stated below
step two:
We are going to collect like terms before factorization we have
We can now factorize the expression we have